2014
DOI: 10.7453/gahmj.2013.075
|View full text |Cite
|
Sign up to set email alerts
|

Non-pharmacological Intervention for Chronic Pain in Veterans: A Pilot Study of Heart Rate Variability Biofeedback

Abstract: Objective:Chronic pain is an emotionally and physically debilitating form of pain that activates the body's stress response and over time can result in lowered heart rate variability (HRV) power, which is associated with reduced resiliency and lower self-regulatory capacity. This pilot project was intended to determine the effectiveness of HRV coherence biofeedback (HRVCB) as a pain and stress management intervention for veterans with chronic pain and to estimate the effect sizes. It was hypothesized that HRVC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 39 publications
3
57
0
Order By: Relevance
“…To derive the other HRV frequency components (LF, and LF/HF), the IBI event series was resampled at 2 Hz to generate an equally spaced intervals time series. RSA and LF were calculated based on the Porges-Bohrer method (53,54); RSA uses a third-order, 21 These variables included:1) respiratory sinus arrhythmia (i.e., RSA or high frequency HRV defined by the frequencies of spontaneous breathing (.12-.4 Hz), 2) low frequency HRV (i.e., occurring within the frequencies of spontaneous vasomotor and blood pressure oscillations; .06-.10 Hz), and 3) ratio of LF and HF (LF/HF)…”
Section: Data Collection and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…To derive the other HRV frequency components (LF, and LF/HF), the IBI event series was resampled at 2 Hz to generate an equally spaced intervals time series. RSA and LF were calculated based on the Porges-Bohrer method (53,54); RSA uses a third-order, 21 These variables included:1) respiratory sinus arrhythmia (i.e., RSA or high frequency HRV defined by the frequencies of spontaneous breathing (.12-.4 Hz), 2) low frequency HRV (i.e., occurring within the frequencies of spontaneous vasomotor and blood pressure oscillations; .06-.10 Hz), and 3) ratio of LF and HF (LF/HF)…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…These chronic systemic functional problems are reflected in the regulation of the heart by the most rapidly responsive component of the nervous system, the ventral vagal complex, as measured by RSA (19). Previous studies have targeted the reduced RSA using biofeedback interventions, and HRV components have been used to measure the efficacy of chronic pain therapies (21)(22)(23)(24). Yet, little is known if targeting network pathologies by non-invasive brain stimulation can influence ANS balance in patients with CLBP.…”
Section: Introductionmentioning
confidence: 99%
“…Among recent studies of biofeedback and pain, Berry et al utilized heart rate variability training with veterans who were receiving treatment for chronic pain [27]. They found that after four biofeedback sessions, the treatment group members averaged statistically significant reductions in perceived pain, stress, negative emotions, and physical activity limitations.…”
Section: Biofeedback Treatmentsmentioning
confidence: 95%
“…Efficacy of biofeedback has been demonstrated in headaches, fibromyalgia, temporomandibular disorders, and other chronic pain states . The application of biofeedback in gastrointestinal disorders is predominantly within dyssynergic defecation, fecal incontinence, and appears promising for functional anorectal pain .…”
Section: Behavioral Interventionsmentioning
confidence: 99%